Anxiety and depression are common in fibromyalgia patients and correlate with symptom severity score - Gurmeet Singh; Sheetal Kaul (Indian Journal of Rheumatology)
Background: Anxiety and depression are seen commonly in fibromyalgia patients. We conducted this study to find out the prevalence of anxiety and depression in fibromyalgia and correlate anxiety and depression with symptom severity (SS) scale. Methods: Eighty fibromyalgia patients and 72 controls were included in this cross-sectional study. Hospital anxiety and depression scale were used to assess anxiety and depression. SS scale was used to assess SS of fibromyalgia. Quality of life (QOL) was measured using the World Health Organization QOL-BREF. The severity of pain, fatigue, and disturbed sleep were measured by 10 centimeter long visual analog scale. Results: Fibromyalgia patients when compared to controls had higher prevalence of both anxiety (87.5% vs. 23.6%, P < 0.0001) and depression (72.5% vs. 5%, P < 0.0001). Both anxiety and depression had positive correlation with SS scale score, (r = 0.51, P < 0.0001) and (r = 0.42, P < 0.0001), respectively. Patients with anxiety and depression had poor QOL, more pain, and more disturbed sleep as compared to patients without anxiety and depression. Gender, disease duration, fatigue, and tender points had no association with anxiety and depression in fibromyalgia patients. Patients with depression had higher age as compared to patients without depression (P = 0.02). Conclusion: Anxiety and depression are common in fibromyalgia patients and correlate with the SS scale score. Fibromyalgia patients with anxiety and depression have poor QOL, more pain, and disturbed sleep.